'Of course you had to keep the cake tins full' : Pakeha women and afternoon tea from 1930-50 : a thesis presented in partial fulfilment of the requirements for the degree of M.Phil. in Visual and Material Culture at Massey University, Wellington, New Zealand - Watson, Megan (Massey University, 2011)
This thesis contributes to an understanding of female Pakeha cultural history through the study of an important social occasion: afternoon tea. It explores afternoon teas hosted in homes around the Manawatu from 1930 -1950, through oral interviews, archival and object-based research, arguing that it was a performance of contemporary female identity as well as a social occasion. Certain items of material culture were ubiquitous: fine china tea sets, embroidered linen, baking and finely sliced bread, and these items demonstrate the critical importance women placed on cooking, cleaning and their own creativity. Overall this case study reveals that Pakeha culture is a hybrid one, and through the examination of decorative motifs on tea sets and table linen, and contemporary cake and biscuit recipes, understandings of contemporary cultural influences are drawn out. The key influences discussed are English, Scottish, Irish and, to a lesser extent, Danish, although the influence of American popular culture is also apparent. As well as the practices of contemporary femininity and creativity, and the influence of different cultural mores, this thesis shows how class distinctions were also in play in rural Manawatu at this time, and how they were apparent at afternoon tea. The period chosen also allows for an examination of how wider economic and social events – poverty during the 1930s Depression and rationing during the World War Two – affected preparations for and the taking of afternoon tea. This research also shows the varying degrees different sectors of society were affected by these events. The study of afternoon tea adds important dimensions to our understanding of the wider historical discourses on gender, class, and Pakeha cultural identities and makes a valuable contribution to women‘s history by emphasising the ubiquitous, but largely undocumented activities of women‘s domestic lives. Additionally, this thesis demonstrates the fresh perspectives that can be gained by using a wide range of sources, such as material culture, cookery books, oral narratives and contemporary periodicals.
Keywords: Afternoon teas; New Zealand; History; 1930s; 1940s